2013
DOI: 10.1007/s11746-013-2360-7
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Interesterified Blends of Fully Hydrogenated Crambe abyssinica Oil and Soybean Oil

Abstract: The chemical interesterification of blends of soybean (SO) and fully hydrogenated crambe oil (FHCO) in the ratios of 80:20, 75:25, 70:30, 65:35, and 60:40 (w/ w), respectively, was investigated. FHCO is a source of behenic acid. The blends and the interesterified fats were analyzed for fatty acid and triacylglycerol composition, regiospecific distribution, slip melting point, solid profile, and consistency. The regiospecific analysis of the TAG indicated random insertion of saturated fatty acids at sn-2 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 22 publications
3
10
0
1
Order By: Relevance
“… the catalyst sodium methoxide used industrially ranges from 0.1 to 0.4% may produce greater than 9% of these minority lipids. Masuchi et al and Guedes et al evaluated the CI of different lipid materials with 0.4% of sodium methoxide, and the results of the levels of DAG were from 4.8 to 9.6%.…”
Section: Resultsmentioning
confidence: 99%
“… the catalyst sodium methoxide used industrially ranges from 0.1 to 0.4% may produce greater than 9% of these minority lipids. Masuchi et al and Guedes et al evaluated the CI of different lipid materials with 0.4% of sodium methoxide, and the results of the levels of DAG were from 4.8 to 9.6%.…”
Section: Resultsmentioning
confidence: 99%
“…The composition of TAGs present in interesterified lipids was analyzed according to the 1,3-random, 2-random theory (non-random redistribution), and 1,2,3-random theory (random redistribution), based on the analysis of the regio-specific distribution described in item 3.4 (D' Agostini and Gioielli, 2002;Guedes et al, 2014).…”
Section: Triacylglycerol Compositionmentioning
confidence: 99%
“…However, when two lipid classes with such distinct chemical composition, such as oils and hardfats, are mixed, the physicochemical properties of the mixture are not necessarily the same as those of the original components, which may result in incompatibility. A monotonic behavior, when high‐melting triacylglycerols are solubilized in the liquid fraction, were observed in binary systems containing soybean oil and soybean hardfat (Ribeiro, Grimaldi, Gioielli, & Gonçalves, ), soybean oil and crambe hardfat (Guedes et al., ), and high oleic sunflower oil and palm hardfat (Masuchi et al., ). The authors found a lower incompatibility in all binary systems by the chemical interesterification, which promoted greater heterogeneity in the composition of triacylglycerols, increasing their solubility in the solid state, thus leading to the formation of solid‐solid solutions.…”
Section: Lipid Modification Processesmentioning
confidence: 99%